Meanderings of a Curious Chemist - Zard, Samir Z. (Synlett, 2022)
This account relates briefly the personal trajectory of the author and the thought processes that went into solving synthetic problems and developing new reactions more generally useful in organic synthesis.1 Preamble and Early Education2 In France with Sir Derek Barton3 Chemistry at Ecole Polytechnique and at the ICSN4 Final Remarks
Keywords: steroids; nitroalkenes; alkynes; radicals; allylations; vinylations; deoxygenation; betaines